Country Partnership Framework for the Republic of Guinea for the Period FY2018-FY23 - World Bank Group (World Bank, Washington, DC, 2018)
Guinea's experience with multiparty democracy is relatively recent and has been marked by socio‐political tensions on several occasions. This Country Partnership Framework (CPF) presents the World Bank Group (WBG) program for Guinea for the Fiscal Year (FY) period of 2018‐2023. The distinctive feature of this CPF is its focus on accelerating the transition to a more diversified, higher value‐added economy while also addressing the multiple drivers of fragility. Maintaining flexibility and the ability to respond quickly to crises is key to the success of World Bank support in fragile environments such as Guinea. Therefore, this CPF leaves some un‐programmed allocations, which will allow the WBG to support the government in implementing its new National Development Plan in a flexible manner so that it can respond to any change of circumstances. There is a need to strengthen the regulatory framework to support successful Public‐Private Partnership (PPP) investments. Working jointly with the World Bank and MIGA, IFC should promote the use of PPP solutions to foster private led‐investments in power generation, specifically in hydro and solar energy. The WBG will strengthen and further mainstream the existing joint review meetings of the portfolio, as well as for the Country Portfolio Performance Reviews (CPPRs).